Efficient deoxygenation of waste cooking oil over Co3O4-La2O3-doped activated carbon for the production of diesel-like fuel - Abdulkareem Ghassan Alsultan; Nurul Asikin Mijan; G. Mustafa–Alsultan; Hwei Voon Lee; Karen Wilson; Yap, Taufiq Yun Hin (Royal Society of Chemistry, 2020)
Untreated waste cooking oil (WCO) with significant levels of water and fatty acids (FFAs) was deoxygenated over Co3O4-La2O3/ACnano catalysts under inert flow N2 condition and micro-batch closed system for production of green diesel. The primary reaction mechanism was found to be prefer in decarbonylation/decarboxylation (deCOx) pathway over the Co3O4-La2O3/ACnano catalyzed reaction. Effect of cobalt doping, catalyst loading, different deoxygenation (DO) systems, temperature and time were investigated. Results indicated that varying the cobalt doping levels (between 5 and 25 wt.%) have revealed a maximum catalytic activity for the Co:La ratio of 20:20 wt/wt. % . DO under N2 flow condition yielded 58% of hydrocarbons with majority diesel-range (n-(C15+C17)) selectivity (~63%) using 3 wt.% catalyst loading at a temperature 350 °C within 180 min. Interestingly, 1 wt.% of catalyst under micro-batch closed system yielded 96% of hydrocarbon with 93% n-(C15+C17) selectivity within 60 min at 330°C, 38.4 wt.% of FFA and 5% of water content. An examination of WCOs under series of FFA (0-20%) and water content (0.5-20 wt.%) indicated an enhanced yield of green diesel, and increased involvement of the deCOx mechanism. High water content was found to fasten the decomposition of triglycerides into FFAs and promote DO reaction. The present work demonstrates that WCOs with significant levels of water and FFAs, generated by the food industries, can provide an economical and naturally replenished raw material for the production of diesel.